Improving Municipal Billing System and Revenue Generating Strategy : Chivi Rural District Council Case Study - MUPEDZI, Bright; OLAREWAJU, Magret; PHESA, Masibulele (International Journal of Environmental, Sustainability, and Social Science, 2023)
Municipalities, in general, experience difficulties in own revenue generation. However, this problem is most severe among rural district councils as they tend to have relatively smaller revenue bases, a culture of non-payment on the part of ratepayers, poor service delivery, inefficient billing systems, poor planning and poor debtor’s management. As a result, rural district councils in Zimbabwe including the Chivi Rural District Council (CRDC) are facing self-sustainability concerns due to financial difficulties. There is overwhelming evidence in research to support the notion that properly planned billing systems have a positive impact on revenue generation among municipalities. On the other hand, poorly planned billing systemswill lead to financial difficulties. A case study approach is designed. Secondary data wasgathered in addition to primary data was collected through questionnaires withCRDC employees and ratepayers. Secondary data was collected through existing CRDC and government reports and documents, and the relevant Acts of Parliament. This found that customers had neutral perceptions of the service quality subconstructs of assurance, reliability, empathy and tangiblesat the CRDC. Further, customers had merely high neutrality almost negative perception of the service quality construct of responsiveness. A statistically significant neutral relationship was found between assurance, reliability, responsiveness, empathy, and tangibles with overall customer satisfaction. The reliability had the highest influence on customer satisfaction, followed by tangibles, responsiveness, empathy, and assurance, respectively. In practical perspective, the study recommends better ways of revenue collection to the municipality. Further the study adds to the debate in literature in Pecking Order Theory.